Familial translocation with partial trisomy of 13 and 22: evidence that specific regions of chromosomes 13 and 22 are responsible for the phenotype of each trisomy. - Kim, H J (1977)
A newborn infant with clinical and pathological findings typical trisomy 13 and 22 syndromes had an extra chromosome which was a derivative chromosome from maternal balanced translocation affecting Nos. 13 and 22; 47,XY,+der(22),t(13:22)(q22:q12)Mat. The presence of extra specific euchromatic regions of No. 13(13q22 and/or 13q34) and No. 22 (22q11) seem to be responsible for the trisomy 13 and 22 syndromes.